2021
DOI: 10.1136/jim-2021-001831
|View full text |Cite
|
Sign up to set email alerts
|

Effects of non-surgical treatment of chronic periodontitis on insulin resistance and glucose tolerance in subjects without diabetes (PARODIA 2 study)

Abstract: This study aimed to assess the effects of non-surgical periodontal treatment (NSPT) of chronic periodontitis on insulin sensitivity, glucose tolerance, and serum C reactive protein (CRP) level in individuals without diabetes. Twenty individuals without diabetes with chronic periodontitis underwent NSPT, which consisted of complete scaling, polishing, root planing, and irrigation of the periodontal pockets with a 10% povidone-iodine solution. Periodontal indices (plaque index, gingival bleeding index, pocket de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 22 publications
0
1
0
Order By: Relevance
“…Multiple research studies revealed that timely medical and surgical intervention regarding chronic periodontal diseases improves serum lipid profiles toward positive, controls blood glucose, increases insulin sensitivity, decreases IR, decreases inflammatory markers, including endotoxin, and restores overall microbiota [ 128 , 138 , 191 - 194 ]. Thus, chronic periodontitis and NAFLD cases are improved.…”
Section: Reviewmentioning
confidence: 99%
“…Multiple research studies revealed that timely medical and surgical intervention regarding chronic periodontal diseases improves serum lipid profiles toward positive, controls blood glucose, increases insulin sensitivity, decreases IR, decreases inflammatory markers, including endotoxin, and restores overall microbiota [ 128 , 138 , 191 - 194 ]. Thus, chronic periodontitis and NAFLD cases are improved.…”
Section: Reviewmentioning
confidence: 99%
“…Those with periodontitis and type 2 diabetes have more inflammatory mediators in their saliva and gingival crevicular fluid than nondiabetic periodontitis patients (Chapple & Genco, 2013 ). Studies show that treating periodontitis can improve control over blood sugar levels and reduce resistance to insulin in diabetic patients (Nana et al, 2021 ; Santonocito et al, 2022 ; Teeuw et al, 2010 ).…”
Section: Introductionmentioning
confidence: 99%
“…Periodontitis is a chronic oral disease caused by the corrosion of dental tissues by pathogenic microorganisms that form periodontal pockets and are absorbed by the alveolar bone, eventually leading to tooth loss. Epidemiological studies have shown that the incidence of periodontitis is increasing and that the elderly account for a relatively high proportion of the population with periodontitis[ 1 , 2 ]. Anxiety and depression are adverse emotions such as tension and fear that occur in patients with periodontitis during treatment and are prevalent in patients of all ages, mainly manifested as fear and avoidance of dental treatment.…”
Section: Introductionmentioning
confidence: 99%